2023
DOI: 10.1177/17588359231165978
|View full text |Cite
|
Sign up to set email alerts
|

The pan-immune-inflammation value is associated with clinical outcomes in patients with advanced TNBC treated with first-line, platinum-based chemotherapy: an institutional retrospective analysis

Abstract: Background: Advanced triple-negative breast cancer (aTNBC) has a poor prognosis; thus, there is a need to identify novel biomarkers to guide future research and improve clinical outcomes. Objectives: We tested the prognostic ability of an emerging, complete blood count (CBC)-based inflammatory biomarker, the pan-immune-inflammation value (PIV), in patients with aTNBC treated with first-line, platinum-based chemotherapy. Design: This was a retrospective, monocentric, observational study. Methods: We included co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The remaining 20 articles' entire texts were then assessed in further detail. There were 8 articles involving 2953 patients (21,22,(27)(28)(29)(30)(31)(32). Figure 1 displays the PRISMA flowchart.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…The remaining 20 articles' entire texts were then assessed in further detail. There were 8 articles involving 2953 patients (21,22,(27)(28)(29)(30)(31)(32). Figure 1 displays the PRISMA flowchart.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…A meta-analysis demonstrated that colorectal tumor patients in the high pretreatment PIV group had poor OS and progression-free survival ( 40 ). Several researches supported the predictive role of PIV in breast cancer ( 15 , 41 ). Among a population of patients with advanced triple-negative breast cancer undergoing platinum-based chemotherapy, Provenzano et al.…”
Section: Discussionmentioning
confidence: 92%
“…Among a population of patients with advanced triple-negative breast cancer undergoing platinum-based chemotherapy, Provenzano et al. found that both the baseline and initial on-treatment PIV correlate with OS ( 41 ). Our study also demonstrated that PIV was significantly related to pCR and OS in breast cancer patients undergoing NACT.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Provenzano et al. retrospectively analyzed the association between increased PIV and adverse outcomes, including worse overall survival (HR: 4.46, 95%CI: 2.22-8.99) and progression-free survival (HR: 2.03, 95% CI: 1.08-3.80), besides, resistance to platinum-based chemotherapy in patients with advanced triple-negative breast cancer ( 20 ). Furthermore, PIV has also been discovered as a novel biomarker in reflecting the association between inflammation and noncancer diseases, such as in hypertension, heart failure, myocardial infarction, kidney disease, frailty, and hepatic steatosis ( 13 , 24 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…type in peripheral blood and potentially reflect the systemic inflammatory conditions. Recent years, the focus of PIV-related research has mainly centered on its implications for the prognosis and therapeutic outcomes in oncological patients (11,12,(18)(19)(20)(21)(22)(23) (20). Furthermore, PIV has also been discovered as a novel biomarker in reflecting the association between inflammation and noncancer diseases, such as in hypertension, heart failure, myocardial infarction, kidney disease, frailty, and hepatic steatosis (13,(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%